Extracellular matrix‐blood composite injection reduces post‐traumatic osteoarthritis after anterior cruciate ligament injury in the rat. Issue 6 (18th December 2015) - Proffen, Benedikt L.; Sieker, Jakob T.; Murray, Martha M.; Akelman, Matthew R.; Chin, Kaitlyn E.; Perrone, Gabriel S.; Patel, Tarpit K.; Fleming, Braden C.
ABSTRACT: The objective of this study was to determine if an injection of a novel extracellular matrix scaffold and blood composite (EMBC) after anterior cruciate ligament (ACL) injury would have a mitigating effect on post‐traumatic osteoarthritis (PTOA) development in rat knees. Lewis rats underwent unilateral ACL transection and were divided into three groups as follows: (1) no further treatment (ACLT; n = 10); (2) an intra‐articular injection of EMBC on day 0 (INJ0; n = 11); and (3) an intra‐articular injection of EMBC on day 14 (INJ14; n = 11). Ten additional animals received capsulotomy only ( n = 10, SHAM group). The OARSI histology scoring of the tibial cartilage and micro‐CT of the tibial epiphysis were performed after 35 days. The ratio of intact/treated hind limb forces during gait was determined using a variable resistor walkway. The OARSI cartilage degradation sum score and total degeneration width were significantly greater in the ACLT group when compared to the INJ0 ( p = 0.031, and p = 0.005) and INJ14 ( p = 0.022 and p = 0.04) group. Weight bearing on the operated limb only decreased significantly in the ACLT group ( p = 0.048). In the rat ACL transection model, early or delayed injection of EMBC ameliorated the significant decrease in weight bearing and cartilage degradation seen in knees subjected to ACL transection without injection. The results indicate that the injection of EMBC may slow the process of PTOA following ACL injury and may provide a promising treatment for PTOA. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:995–1003, 2016.